IMPLEMENTASI KONSEP EDUPRENEURSHIP DALAM PENGELOLAAN LEMBAGA BIMBINGAN BELAJAR “ANAK HEBAT” KEDUNGWUNI KABUPATEN PEKALONGAN - M. Shidqul Wafa; Navita Putri Lestari; Fani Restian; Naily Fatikhul Izzah (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
This study adopts a qualitative approach with a descriptive research type, aiming to holistically describe the implementation of the edupreneurship concept in the management of the "Anak Hebat" Kedungwuni Tutoring Institute (Bimbel). Specifically, this study seeks to understand how the concept of educational entrepreneurship is translated into managerial practices, innovations in learning strategies, its impact on the formation of student independence, and identifying inhibiting factors. The research location was determined purposively in Kedungwuni District, Pekalongan Regency, with the unique consideration that this institution was established in 2020 as an adaptive response amidst the COVID-19 pandemic crisis, making it an information-rich case. The focus of the research is directed at exploring the motivation for establishment, managerial management strategies, service innovations, and operational challenges. Mrs. Rofi'ah, the manager and founder of Bimbel, was the sole key informant selected through purposive sampling due to her central role and experience. To ensure validity, data were collected through triangulation techniques: in-depth semi-structured interviews (to explore motivations, strategies, and challenges broadly), direct observation (to observe the atmosphere and teacher-student interactions), and documentation (to verify the institution's profile and administrative data). This method allows for the collection of rich, narrative, and contextual data regarding the specific case studied. The results of the study illustrate that edupreneurship practices at the "Anak Hebat" Tutoring Center are not only oriented towards business sustainability but also strengthen aspects of student learning independence through flexible service strategies, personalized approaches, and learning innovations tailored to students' developmental needs. The relevance of these findings emphasizes that the success of a tutoring center is not only measured by profitability, but also by its capacity to act as an edupreneur that is responsive to market needs, while simultaneously being a driver for the development of student learning independence.